Role grupowe a płeć psychologiczna i kompetencje społeczne - Strzelczyk-Muszyńska, Dorota (Acta Universitatis Lodziensis. Folia Psychologica, 2007)
The object of the study was to explore a potential relationship between group roles (the dependent variable) and psychological gender and social competence (the independent variables). The research was made more specific by asking three cognitive questions (Does the prevalence of the researched with IPP and KKS qualities differentiate the questioned women in their group role preferences (t-student)? Are specific group roles dependent on psychological gender (ANOVA)? Is there the joint impact of individual personality variables on displaying group roles (analysis of regression). The research was carried out on year three psychology students of the University of Łódź. The study has resulted in discovering statistically significant differences between representatives of different types of psychological gender and their group role preferences. We have also discovered a different prevalence of variables defined as social competence depending on the adopted group role.